PERBANYAKAN TANAMAN WIEP {Grevillea papuana) SECARA KULTUR JARINGAN - L Agus Sukamto (BERITA BIOLOGI, 2003)
The population of wiep (Grevillea papuana) originated from Papua, decreased because of over cutting or over exploitation for timber, ornamental or medicine. Experiment was carried out to propagate wiep by using tissue culture method. Hypocotyls, cotyledons and nodes from seedlings grown in vitro, were used as explants. These explants were grown on Murashige & Skoog medium which macro and micronutrients were half strength, with or without hormones (BA 1 mg/1, BA 1 mg/1 + NAA 0,5 mg/1, BA 2 mg/1 + NAA 0,5 mg/1, BA 1 mg/1 + 2,4-D 0,5 mg/1, and BA 2 mg/1 + 2,4-D 0,5 mg/1).All explants did not produce callus on medium without hormones, but produced callus with hormones except BA treatment on cotyledon explants. Bigger callus were produced by explants that were treated by combination BA with NAA or 2,4-D compare to those treated by BA only. Nodes and hypocotyls could produce shoots, but cotyledons did not. Three kinds of explants did not produce any roots. Node is the best explants for producing shoots.Combination of BA 1 mg/1 and 2,4-D 0,5 mg/1 caused synergistic effect to stimulate shoot production of wiep hypocotyls explants.